Effect of Macroporosity on Pedotransfer Function Estimates at the Field Scale - Zhang, X. (2020)
The objectives of this study were to evaluate the performance of established PTFs in estimating Ks in a specific field and improve PTFs to arrive at a locally adapted estimation result for Ks. Forty‐one soil samples were collected from 10 locations at five depths at a farmland in western Kentucky for hydraulic conductivity and physical property measurements. The performance of seven PTFs in estimating Ks was evaluated using the root mean square error (RMSE), Nash–Sutcliffe efficiency (NSE), and the coefficient of determination (R2). At this scale, all the selected PTFs exhibited unsatisfactory prediction of Ks (high RMSE, low NSE and R2). In the field studied, approximately 60% of variance in Ks could be explained by soil texture and macropore components based on factor analysis. Clay content and macroporosity were identified as the most representative variables for each component. The performance of a PTF in estimating Ks for the field site investigated was significantly improved by including macroporosity (pores with diameter >75 μm) as a predictor. The results confirmed that soil structure was crucial in characterizing soil hydraulic conductivity.